Policy of the Russian Empire Regarding the Polish Population of Right-Bank Ukraine in the Second Half of the Nineteenth Century - Aloshyna, Oksana (Journal of Education Culture and Society, 2022)
Aim. The purpose of the scientific article is to reveal the specifics of the policy of the Russian Empire towards the Polish population on the territory of the Right-Bank of Ukraine.Methods. The research methodology is based on the principles of scientificity, historicism, systematics. During the research work, both general scientific (analysis and synthesis, systematisation and generalisation) and special scientific methods were used: problem-thematic, as well as system-structural.Results. The politics of the Russian government towards the poles had an important place in the socio-political life of Right-bank Ukraine. Using legislative documents and ordinances, the Russian government introduced a number of restrictive measures that were supposed to control and weaken the influence of Poles on the socio-economic life of the region.Conclusions. The Russian authorities tried to neutralise the influence of the Polish population and the Roman Catholic Church. Determining the presence of Poles and regulating their number depended on the strict control of the Russian government. The Poles were seen as a “dangerous element” threatening the policy of tsarist autocracy. That is why the authorities decided to undermine their socio-economic position by depriving them of a significant number of privileges.